Available Active Sites on ε‐Fe3N Nanoparticles Synthesized by a Facile Route for Hydrogen Evolution Reaction. Issue 11 (30th April 2021) - Qiang, Ruo; Wang, Hui; Xu, Kang; Yuan, Qunyao; Yu, Youxing; Li, Lei; Wang, Jiaou; Zheng, Lirong; Sherrell, Peter C.; Chen, Jun; Bi, Xiaofang
Abstract: Exploring efficient noble‐metal‐free water‐splitting electrocatalysts from earth‐abundant elements is of great importance to realize wide applications in the generation of hydrogen fuel for clean energy. Here, a facile route is reported to synthesize ε‐Fe3 N single‐phase nanoparticles by thermal ammonolysis of Fe precursors. The roles of nitrogen atoms in tailoring the hydrogen evolution reaction (HER) activities of ε‐Fe3 N have been systematically investigated. HER activity is enhanced by reducing the effective coordination number of nitrogen atoms from 2.61 to 1.67, where the standard coordination number in ε‐Fe3 N is 2. Density functional theory calculations reveal that the reduction of nitrogen content lowers the energy of Tafel process on the ( 1 ¯ 100)‐FeN‐exposed and (11 2 ¯ 0) N‐exposed surfaces. Both surfaces are thermodynamically favored for the HER. Furthermore, the active sites of Tafel process change from the kinetically less favored hollow sites of Fe atoms to the kinetically more favored top site of N atoms and the bridge site of Fe atoms on both ( 1 ¯ 100)‐FeN and (11 2 ¯ 0) N‐exposed surfaces. The findings propose a novel strategy to enhance HER activity by using nitrogen deficiency, which is of great importance for the development of highly active transition metal based electrocatalysts. Abstract : A facile route to synthesize ε‐Fe3 N single‐phase nanoparticles by thermal ammonolysis of Fe precursors is reported. Through specifying available active sites based on experimental and theoretical research, a novel strategy to enhance hydrogen evolution reaction activity by using nitrogen deficiency is proposed, which is of importance for the development of highly active transition metal based electrocatalysts.